2020
DOI: 10.1259/bjr.20200321
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of pituitary macroadenomas aggressive behaviour: a conventional MRI and DWI 3T study

Abstract: Objective: Pituitary macroadenomas (PAs) are usually defined as benign intracranial tumors. However, they may present local aggressive course. High Ki67 labelling index (LI) values have been related to an aggressive tumor behavior. A recent clinicopathological classification of PA based on local invasiveness and proliferation indexes, divided them in groups with different prognosis. We evaluated the utility of conventional MRI (cMRI) and diffusion-weighted imaging (DW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…To the best of our knowledge, Ugga et al and Conficoni et al both proposed methods predicting the Ki-67 index for patients with PAs based on MRI and diffusion-weighted imaging (8,10). The machine learning model built by Ugga et al showed high accuracy (91.67%, 33/36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, Ugga et al and Conficoni et al both proposed methods predicting the Ki-67 index for patients with PAs based on MRI and diffusion-weighted imaging (8,10). The machine learning model built by Ugga et al showed high accuracy (91.67%, 33/36).…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, applying this machine learning model in an actual clinical practice requires supporting software and platform, which must be developed in the future. Conficoni et al suggested that quantitative measures of apparent diffusion coefficient (ADC) values could predict the Ki67 value (10). However, this value was not routinely assessed in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…This value may reflect the growth pattern of tumors with higher invasiveness, which should be verified by further molecular studies. Ki-67 is a classical index for the description of tumor proliferation in pituitary adenomas ( 19 , 20 ). However, current estimations of Ki-67 are mostly based on visual detection under a microscope, which lacks objectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Brunetti et al have reported that machine learning analysis of preoperative T2 MRI texture-derived parameters can effectively predict the Ki-67 proliferation index category of pituitary macroadenomas [ 8 ]. Bacci et al demonstrated that the quantitative measurement of the apparent diffusion coefficient value in MRIs could be used to predict the Ki-67 index of PAs [ 9 ]. However, the implementation of these prediction methods requires specific software and platforms, and practical clinical applications are difficult to implement.…”
Section: Introductionmentioning
confidence: 99%